Possibilities and limits in the analysis of social exclusion spatiality - Valentina Vasile; Mihaela Mihai; Daniela-Ioana Manea; Emilia Titan; Cristina Boboc (Revista română de economie, 2017)
Social exclusion may manifest through spatial concentration of deprived population in communities located in certain areas. The globalization has reshaped the social and spatial geography of cities which led to major implications for research on social exclusion. Thus, in any practical formulation of social inclusion policies, it is necessary to consider the idea that social exclusion is inherently spatial. By addressing the territorial dimension of social exclusion, some important theoretical issues about the interaction of the two concepts ("social" and "space") are analyzed. Based on theoretical-conceptual contributions developed recently, this paper analyzes this dimension of social exclusion.
2665773-9; 2344-4657; Revista română de economie; 717197875